2017
DOI: 10.1007/s00705-017-3424-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and phylogenetic analysis of a multifocal cutaneous orf virus with mixed bacterial infection outbreak in goats in Fujian province, China

Abstract: Outbreaks of orf virus on goat farms are common in China. In this study, we investigated a severe multifocal cutaneous orf virus outbreak with a correlative mixed bacterial infection which persisted for up to 6 months, and which had a high morbidity (93.7%) and mortality (15%) among kids in a herd of crossbreed goats in Fujian province in China. The disease was diagnosed as an orf virus (ORFV XD strain) infection associating with Streptococcus pluranimalium and Staphylococcus, identified using standard virolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…We can thus say that there is no connection between the sex, age or severity of the lesions and the number of species of bacteria that infect lesions caused by orf virus. Lesional scores of sheep with suprainfected orf lesions tended to cluster around 2 and 3 confirming that the bacteria that populate such lesions also complicate the course of the disease as noted by Fleming et al, 2015 andChi et al, 2017. However, as regards sex of the affected animals, females seemed to be more susceptible to a secondary infection, probably due to the fact that the disease developed in late spring, during the shearing when the stress caused by lamb suckling and shearing can decrease the immunity of mothers.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…We can thus say that there is no connection between the sex, age or severity of the lesions and the number of species of bacteria that infect lesions caused by orf virus. Lesional scores of sheep with suprainfected orf lesions tended to cluster around 2 and 3 confirming that the bacteria that populate such lesions also complicate the course of the disease as noted by Fleming et al, 2015 andChi et al, 2017. However, as regards sex of the affected animals, females seemed to be more susceptible to a secondary infection, probably due to the fact that the disease developed in late spring, during the shearing when the stress caused by lamb suckling and shearing can decrease the immunity of mothers.…”
Section: Discussionmentioning
confidence: 76%
“…Following the determinations, we found that S. aureus and P. aeruginosa dominated in secon dary infections, underlying their highly infectious character if they encounter a breach in the organism (Zecconi and Scali, 2013). Contagious ecthyma being a disease that affects the skin, it creates breaches for S. aureus and can complicate the evolution of this disease (Chi et al, 2017). Being a bacteria that easily adapts to any biological environment can even cause treatment-resistant rebellious mastitis (Weese et Note: Correlations are being calculated at a 95% level of significance, P values higher then 0,05 indicating that correlations beween the two sets of values cannot be generalized and every correlation between two datasets is the result of hazard r-correlation coefficient al., 2010).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, mortality may increase by 20% ~ 50% as a result of secondary bacterial infection, stress, immunosuppression or in concomitant evolution with other diseases and may exceed 90% in the case of malignant orf (Hosamani et al, 2009). Frequent suprainfections occur with bacteria such as Staphylococcus and Streptococcus (Chi et al, 2017) but also with other bacteria (Venkatesan et al, 2018). Scarification or microabrasions in the epidermis are a condition for the onset of the disease.…”
Section: Introductionmentioning
confidence: 99%